2020
DOI: 10.1161/strokeaha.119.026969
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Implementation of the Ottawa Subarachnoid Hemorrhage Rule and 6-Hour Computed Tomography Rule

Abstract: Background and Purpose— The Ottawa subarachnoid hemorrhage (SAH) rule identifies patients with headache requiring no testing for SAH, while the 6-hour computed tomography (CT) rule guides when to forgo a lumbar puncture. Our objectives were to: (1) estimate the clinical impact of the Ottawa SAH rule and the 6-hour-CT rule on testing rates (ie, CT, lumbar puncture, CT angiography); (2) validate the 6-hour-CT rule for SAH when applied prospectively in a new cohort of patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
5
36
0
Order By: Relevance
“…External validation has taken place in over 4,000 patients and, with the exception of one study, has demonstrated a sensitivity of 100%. [8][9][10][11][17][18][19] Specificity has been lower and has ranged from 7.6% to 44%. These external validation studies, together with the results from our present study, represent a robust external validation of the Ottawa rule and provide an evidence base for its introduction into clinical practice to aid in the decision for CT of the head in cases of suspected SAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…External validation has taken place in over 4,000 patients and, with the exception of one study, has demonstrated a sensitivity of 100%. [8][9][10][11][17][18][19] Specificity has been lower and has ranged from 7.6% to 44%. These external validation studies, together with the results from our present study, represent a robust external validation of the Ottawa rule and provide an evidence base for its introduction into clinical practice to aid in the decision for CT of the head in cases of suspected SAH.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a prospective study from Perry et al, there was no increase in rate of neuroimaging following the introduction of the Ottawa rule to clinical practice. 19 Taken together, although the Ottawa rule is limited by its specificity, it does not necessarily lead to increased rates of neuroimaging. Indeed, given the consistent demonstration of the rule's sensitivity across several studies, its role in reducing neuroimaging and subsequent investigation rates for low-risk patients may be more apparent in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers argue that CT might be sufficient to rule out subarachnoid bleeding if the scan is normal and is done within 6 h of the TCH onset (19,20,27,34). However, other secondary headache disorders can be responsible for the TCH, and even in those studies, 4.0% (19) to 9.3% (27) of patients showed a cause of TCH different from SAH, half of them diagnosed only by LP (25). The 6-h CT rule showed a 95.5% sensitivity rate in a prospective multicenter study in the diagnosis of SAH, reporting 188 cases of SAH out of 3672 patients with TCH (20).…”
Section: Discussionmentioning
confidence: 99%
“…We also reported the percentage of patients that were evaluated by a neurologist, the percentage of patients that were admitted, and the percentage of patients that were discharged without further examination. As an exploratory endpoint, we assessed if the CT was requested within 6 h of arrival to the ER, if it was completed within 6 h of arrival (19), and whether or not CT detected the presence of SAH in patients with SAH as a final diagnosis (20).…”
Section: Methodsmentioning
confidence: 99%